A reconsideration and response to Parrott AC (2013) "Human psychobiology of MDMA or 'Ecstasy': an overview of 25 years of empirical research". (March 2014) - Doblin, Rick; Greer, George; Holland, Julie; Jerome, Lisa; Mithoefer, Michael C.; Sessa, Ben
Abstract Parrott recently published a review of literature on MDMA/ecstasy. This commentary is a response to the content and tenor of his review, which mischaracterizes the literature through misstatement and omission of contrary findings, and fails to address the central controversies in the literature. The review makes several erroneous statements concerning MDMA‐assisted psychotherapy, such as incorrect statements about research design and other statements that are baseless or contradicted by the literature. Though it critiques an attempt by other authors to characterize the risks of MDMA, the review fails to produce a competing model of risk assessment, and does not discuss potential benefits. Parrott does not represent an even‐handed review of the literature, but instead recites dated misconceptions about neurotoxicity concerns involving the recreational drug ecstasy, which do not relate directly to the use of pure MDMA in a therapeutic setting. Unchallenged, Parrott's report may deter researchers from further investigating an innovative treatment that in early clinical trials has demonstrated lasting benefits for people with chronic, treatment‐resistant post‐traumatic stress disorder. Copyright © 2014 John Wiley & Sons, Ltd.